2015
DOI: 10.3727/096368914x684619
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal Stromal Cells Improve Renovascular Function in Polycystic Kidney Disease

Abstract: Polycystic kidney disease (PKD) is a common cause of end stage renal failure, for which there is no accepted treatment. Progenitor and stem cells have been shown to restore renal function in a model of renovascular disease, a disease that shares many features with PKD. The objective of this study was to examine the potential of adult stem cells to restore renal structure and function in PKD. Bone marrow-derived mesenchymal stromal cells (MSCs, 2.5×105) were intrarenally infused in 6 week-old PCK rats. At 10 we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 51 publications
0
24
0
1
Order By: Relevance
“…MSCs have become a promising source for cell-based therapies (32,33). It has been reported that the co-culture of islets with MSCs has beneficial effects, including maintaining morphological changes, conserving islet function and preventing an early inflammatory reaction (34,35).…”
Section: Discussionmentioning
confidence: 99%
“…MSCs have become a promising source for cell-based therapies (32,33). It has been reported that the co-culture of islets with MSCs has beneficial effects, including maintaining morphological changes, conserving islet function and preventing an early inflammatory reaction (34,35).…”
Section: Discussionmentioning
confidence: 99%
“…In the last years, two studies have been published that show the possible therapeutic effects of allogeneic stem cells in rats. Franchi et al have shown that a single injection of BM-MSC isolated from healthy SD rats could improve the kidney function in PCK rats, partially restoring renal function ( 273 ). This study points out two of the potential effects of stem cells: the paracrine effects, by the release of cytokines, such as SDF1, VEGF, and HGF, and the ability of the cells, after injection, to acquire characteristics of endothelial cells, suggesting transdifferentiation of these cells.…”
Section: Msc Therapy In the Treatment Of Kidney Diseases: State Of Thmentioning
confidence: 99%
“…Anti-apoptotic [ 10 ], anti-fibrotic [ 11 ], and anti-inflammatory [ 12 ] capabilities of MSCs [ 7 ] provide the basis for their administration to control the progression of polycystic kidney disease (PKD). Franchi et al have reported that transplanted MSCs restored kidney function in a PKD model and improved damaged vasculature of these kidneys [ 13 ]. Previously we showed the promising efficacy of transplanted MSCs in experimental models of chronic kidney disease (CKD) and acute kidney injury (AKI) [ 14 16 ].…”
Section: Introductionmentioning
confidence: 99%